Medical Humanity and Inhumanity in the German-Speaking World - Puw Davies, Mererid; Shamdasani, Sonu (Fringe, 2020)
Medical Humanity and Inhumanity in the German-Speaking World is the first volume dedicated to exploring the interface of medicine, the human and the humane in the German-speaking lands. The volume tracks the designation and making through medicine of the human and inhuman, and the humane and inhumane, from the Middle Ages to the present day. Eight individual chapters undertake explorations into ways in which theories and practices of medicine in the German-speaking world have come to define the human, and highlight how such theories and practices have consolidated, or undermined, notions of humane behaviour. Cultural analysis is central to this investigation, foregrounding the reflection, refraction and indeed creation of these theories and practices in literature, life-writing and other discourses and media. Contributors bring to bear perspectives from literary studies, film studies, critical theory, cultural studies, history, and the history of medicine and psychiatry. Thus, this collection is historical in the most expansive sense, for it debates not only what historical accounts bring to our understanding of this topic. It encompasses too investigation of life-writing, documentary, and theory and literary works to bring to light elusive, paradoxical, underexplored - yet vital - issues in history and culture.